Draft Annual Plan 2003-2004 (Text) Government of Madhya Pradesh - Planning Commission (Planning Commission, 2003)
Positive direction in the growth of the economy and progress in the different sectors rest on socio economic development, which calls for heavy public investment in the core sectors as also in infrastructure. Development of the social sector along with technology absorption in agriculture and industry, which are the principal sectors of our economy, is nowadays considered as the primary objective of any economic development effort. In Madhya Pradesh the development programmes have been carefully implemented during the five-year plan periods. However, the objective of enhancing the quality of life of people has not been fully achieved so far. This annual plan aims to reduce poverty substantially and to bring the state al par with the other developed slates.
Government of Madhya Pradesh, Planning, Economics and Statistics Department